Phytocannabinoids and epilepsy. (4th December 2014) - dos Santos, R. G.; Hallak, J. E. C.; Leite, J. P.; Zuardi, A. W.; Crippa, J. A. S.
Summary What is known and objective Antiepileptic drugs often produce serious adverse effects, and many patients do not respond to them properly. Phytocannabinoids produce anticonvulsant effects in preclinical and preliminary human studies, and appear to produce fewer adverse effects than available antiepileptic drugs. The present review summarizes studies on the anticonvulsant properties of phytocannabinoids. Methods Literature search using the PubMed database to identify studies on phytocannabinoids and epilepsy. Results and discussion Preclinical studies suggest that phytocannabinoids, especially cannabidiol and cannabidivarin, have potent anticonvulsant effects which are mediated by the endocannabinoid system. Human studies are limited in number and quality, but suggest that cannabidiol has anticonvulsant effects in adult and infantile epilepsy and is well tolerated after prolonged administration. What is new and conclusion Phytocannabinoids produce anticonvulsant effects through the endocannabinoid system, with few adverse effects. Cannabidiol and cannabidivarin should be tested in randomized, controlled clinical trials, especially in infantile epileptic syndromes.